A projection-type method for solving multi-valued variational inequalities and fixed point problems. (2nd December 2017) - Zhang, Lixin; Fang, Changjie; Chen, Shenglan
Abstract: In this paper, we introduce a projection algorithm for finding a common element of the set Fix ( T ) of fixed points of a -strict pseudocontraction mapping and the set S of solutions of a multi-valued variational inequality problem without monotonicity. We show that the sequence generated by our method is globally convergent to some common element of Fix ( T ) and S, provided that the mapping F is continuous with nonempty compact convex values. Preliminary numerical experiments are reported.